Adequate control of hypertension among older adults: ELSI-Brazil - Josélia Oliveira Araújo Firmo; Juliana Vaz de Melo Mambrini; Sérgio Viana Peixoto; Antônio Ignácio de Loyola Filho; Paulo Roberto Borges de Souza Junior; Fabíola Bof de Andrade; Maria Fernanda Lima-Costa (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To estimate the prevalence of adequate control of hypertension among older adults and to examine its association with predisposing and enabling factors and the need to use health services. METHODS The analysis was carried out with 4,148 participants (≥ 50 years) from the baseline of the Brazilian Longitudinal Study of Aging (ELSI-Brazil), who reported being hypertensive and using antihypertensive medication. Adequate control of hypertension was defined as systolic and diastolic blood pressure below 140 mmHg and 90 mmHg, respectively. The following exploratory variables were included: age, sex, health behaviors, and body mass index (predisposing factors); region of residence, rural or urban residence, education level, socioeconomic status of the household, and coverage by private health plan (enabling factors); and medical diagnosis of diabetes (need). The multivariate analysis was performed using Poisson regression and binary logistic regression. RESULTS The prevalence of adequate control of hypertension was equal to 51.1% (95%CI 48.5-53.6). After adjusting for potential confounders, we observed statistically significant associations (p < 0.05) for education level > 4 years [prevalence ratio (PR) = 1.12 in relation to the lowest level], highest quintile of the socioeconomic status (PR = 1.22 in relation to the lowest quintile), coverage by private health plan (PR = 1.13), residence in the South (PR = 1.19) and Midwest regions (PR = 1.20) in relation to the Southeast region, and obesity (PR = 1.10). CONCLUSIONS Half of the population studied had adequate control of hypertension. The improvement of this control is an important challenge, which should consider overcoming social and regional inequalities associated with it.